Sea Salt : Poems of a Decade, 2004-2014 - Mason, David, 1954- (Book collections on Project MUSE., 2014)
Long regarded as one of the best narrative and dramatic poets at work in the United States, David Mason has also been regularly producing soulful lyrics. In the ten years since the publication of his last collection of shorter poems, Mason has refined his art in the fires of wrenching personal change. The result is an almost entirely new poetic voice and his most rigorous and memorable book to date. Emotionally resonant and elegant in phrasing, the poems of Sea Salt, which have appeared in publications such as Best American Poetry, The New Yorker, Harper's, and Poetry, are a powerful evocation of crisis and change. These "poems of a decade" demonstrate that the author of Ludlow: A Verse Novel and The Scarlet Libretto is also a lyric poet at the top of his game. --Amazon.